The Ethiopian homily on the Ark of the Covenant : critical edition and annotated translation of Dersanä Ṣeyon - Amsalu Tefera. (Texts and Studies in Eastern Christianity, 2015)
In The Ethiopian Homily on the Ark of the Covenant , Amsalu Tefera offers an editio princeps of the Ethiopic text of Dǝrsanä Ṣǝyon together with an annotated English translation. This homily, most likely composed in the fifteenth century, links the term Zion with the Ark of the Covenant and recounts at length its wanderings from Sinai to Ethiopia. As a Christian document, many of the events are interpreted as symbolic of Mary and the heavenly New Jerusalem. First edited by the author for his 2011 doctoral dissertation, the critical text and apparatus present a complete collation of the ten known witnesses to this homily. Detailed notes are supplied on significant and difficult terms in the translation.